THE INTELLIGIBILITY, COMPREHENSIBILITY, AND INTERPRETABILITY OF AN INDONESIAN SENIOR HIGH SCHOOL ENGLISH TEACHER (RETAIN, 2017)
THE INTELLIGIBILITY, COMPREHENSIBILITY, AND INTERPRETABILITY OF AN INDONESIAN SENIOR HIGH SCHOOL ENGLISH TEACHER Eugenia Rani Rarasati English Department Faculty, Faculty of Language and Arts, State University eugeniararasati@mhs.unesa.ac.id Ahmad Munir, S.Pd., M.Ed., Ph.D English Department Faculty, Faculty of Language and Arts, State University ahmadmunir@unesa.ac.id Abstrak Intelligibility, comprehensibility, dan interpretability merupakan komponen penting untuk mencapai komunikasi yang effektif. Seseorang perlu menggunakan ucapan yang mudah dipahami sehingga pendengar mampu menafsirkannya secara benar. Kemampuan intelligibilitas ini merupakan sesuatu yang perlu dimiliki guru untuk menciptakan pembelajaran yang effektif. Oleh karena itu, penelitian ini dilakukan untuk mengetahui apakah Bahasa Inggris guru sudah dapat dimengerti, dipahami, dan ditafsirkan dengan baik atau belum. Tiga puluh satu siswa kelas sepuluh dari sekolah menengah atas berstandar ISO dan seorang guru bahasa Inggris senior menjadi subyek dari penelitian ini. Data diperoleh berdasarkan kesan dan reinterpretasi siswa terhadap penjelasan guru yang yang mereka tulis di lembar kuesioner. Hasilnya menunjukkan bahwa intelligibility, comprehensibility, dan interpretability guru tinggi, terbukti dengan nilai yang diperoleh dari kuesioner, wawancara singkat, dan analisis Bahasa Inggris guru. Kata kunci: Bahasa Inggris guru, Intelligibility, Comprehensibility, Interpretability. Abstract Intelligibility, comprehensibility, and interpretability are the keys to achieve successful communication. Someone needs to use intelligible and comprehensible utterance so that the listener becomes able to interpret it in a correct way. This inteligibility ability is something which actually needs to be required by teachers in order to maintain effective learning. Therefore, this study is conducted to find out whether teacher’s English is already intelligible, comprehensible, and interpretable or not. Thirty one students in the tenth grade of ISO standard senior high school and a senior English teacher were the participants. The data were gained from students’ impression and reinterpretation of teacher’s speech written in a questionnaire. The results revealed that teacher’s intelligibility, comprehensibility, and interpretability was high, proven by the scores gained from questionnaire, brief interview, and analysis of teacher’s English. Keywords: Teacher’s English, Intelligibility, Comprehensibility, Interpretability.